INVESTIGATION OF NOISE CHARACTERIZATION OF COATED ROTORS - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2021)
In this study, four excessive worn brake rotors of a light commercial vehicle are coated using different thickness, methods and powder coatings. Coated rotors (R1, R2, R3 and R4) compared with OEM brake rotor (R0) in terms of friction coefficient (mu) and braking noise. Three braking test procedures (bedding, hot judder I and II) are applied to five rotors using inertia brake dynamometer. Results in bedding testing procedures showed that R0 rotor provided higher brake noise and higher mu compared with coated rotors. In hot judder I testing procedures, R4 rotor provided higher mu and higher brake noise compared with the other coated rotors and R0. Also, in hot judder II testing procedures, R2 rotor provided higher mu compared with the other rotors, R0 provided higher brake noise compared with the other coated rotors. In addition, based on experimental data, noise levels are estimated by multiple regression method with dummy variables.
Keywords: Brake noise; braking parameters; friction coefficient; coated rotor; multiple regression method; BRAKE SQUEAL; PERFORMANCE; VIBRATION; DISCS